Effect of Modifying Additions on Synthesis and Properties of Cordierite-Mullite Ceramic from Kazakhstan Resources - Biryukova A. A. Alla Alexandrovna; Dzhienalyev T. D. Tolebi Dauletalyevich; Boronina A. V.; Khabas (Habas) T. A. Tamara Andreevna; Pogrebenkov V. M. Valery Matveevich (2017, 2017)
Title screen